2004
DOI: 10.1073/pnas.0402869101
|View full text |Cite
|
Sign up to set email alerts
|

The ion channel of F-ATP synthase is the target of toxic organotin compounds

Abstract: ATP is the universal energy currency of living cells, and the majority of it is synthesized by the F 1 F 0 ATP synthase. Inhibitors of this enzyme are therefore potentially detrimental for all life forms. Tributyltin chloride (TBT-Cl) inhibits ATP hydrolysis by the Na ؉ -translocating ATP synthase of Ilyobacter tartaricus or the H ؉ -translocating counterpart of Escherichia coli with apparent K i of 200 nM. To target the site of this inhibition, we synthesized a tritium-labeled derivative of TBT-Cl in which on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(53 citation statements)
references
References 38 publications
3
50
0
Order By: Relevance
“…von Ballmoos et al showed that subunit a of F 1 F 0 ATP synthase is the target site of TBT for inhibition, by using a synthetic photoaffinity-labeled probe. 13) However, these data were obtained at concentrations of a few µM, and F 1 F 0 ATP synthase may be scarcely inhibited by nM order concentrations of organotin.…”
Section: Atp Synthase Inhibitionmentioning
confidence: 96%
“…von Ballmoos et al showed that subunit a of F 1 F 0 ATP synthase is the target site of TBT for inhibition, by using a synthetic photoaffinity-labeled probe. 13) However, these data were obtained at concentrations of a few µM, and F 1 F 0 ATP synthase may be scarcely inhibited by nM order concentrations of organotin.…”
Section: Atp Synthase Inhibitionmentioning
confidence: 96%
“…The sites of action of organotin compounds are located in the ion channel within subunit a. Here, they are believed to inhibit ATP synthase by competing with Na ϩ or H ϩ for the same binding site (418). Diorganotin-3-hydroxyflavone complexes such as dibutyltin 3-hydroxyflavone bromide and diphenyltin 3-hydroxyflavone chloride show a marked fluorescence enhancement on binding to mitochondrial ATP synthase (405).…”
Section: Organotin Compounds and Structural Relativesmentioning
confidence: 99%
“…This indicated that there may be a very tight association of the compounds with a protein(s) involved in ATP synthesis such as ATP synthase. Others have shown that TBT binds to ATP synthase in bacteria (von Ballmoos et al, 2004). It is quite possible that the OTs tested in this study may also bind quite tightly to some component(s) such as ATP synthase.…”
Section: Discussionmentioning
confidence: 83%
“…These findings are consistent with the results seen with butyltins, DBT and TBT (Dudimah et al, 2006a, b). TBT has been shown to inhibit the function of the mitrochondrial ATP synthase (von Ballmoos et al, 2004;Matsuno-Yagi and Hatefi., 1993). Thus, sustained decreases in ATP levels seen with TBT exposures may be partially due to the ability to inhibit ATP synthase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation